1996
DOI: 10.1021/jf9405867
|View full text |Cite
|
Sign up to set email alerts
|

Fluroxypyr- and Triclopyr-Specific Enzyme-Linked Immunosorbent Assays:  Development and Quantitation in Soil and Water

Abstract: Enzyme-linked immunosorbent assays (ELISAs) were developed to quantitate fluroxypyr [[(4-amino-3,5-dichloro-6-fluoro-2-pyridinyl)oxy]acetic acid] and triclopyr [[(3,5,6-trichloro-2-pyridinyl)oxy]acetic acid] in soil and water. The linear working range of the fluroxypyr ELISA was from 0.1 to 10 ng‚mL -1 with a limit of detection (LOD) of 0.1 ng‚mL -1 and an IC 50 value of 1.6 ng‚mL -1 . The linear working range of the triclopyr ELISA was from 0.1 to 5 ng‚mL -1 with a LOD of 0.1 ng‚mL -1 and an IC 50 value of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The enzyme-linked immunosorbent assay (ELISA) is recognized as a valuable tool in residue analysis and compliments conventional analytical methods (Johnson and Hall, 1996;Parnell and Hall, 1998). ELISA provides rapid sample testing and accurate results and is more cost-effective than conventional chromatographic analysis (Hall et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme-linked immunosorbent assay (ELISA) is recognized as a valuable tool in residue analysis and compliments conventional analytical methods (Johnson and Hall, 1996;Parnell and Hall, 1998). ELISA provides rapid sample testing and accurate results and is more cost-effective than conventional chromatographic analysis (Hall et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The dissipation dynamics of fluroxypyrmeptyl in soil in Beijing and Tianjin could be described by Residue Analysis of Fluroxypyr-meptyl 293 According to the literature, fluroxypyr-meptyl could hydrolyze to the acid form (fluroxypyr) [1,2]. Tao [4] and Bai [5] developed analytical methods for fluroxypyr residues in wheat, in which the recoveries ranged from 84.0 to 94.1%.…”
Section: Dissipation Of Fluroxypyr-meptyl In Soilmentioning
confidence: 99%
“…Fluroxypyr is mostly applied as the methylheptyl ester [fluroxypyr-meptyl ( Fig. 1)] in China [2]. To the best of our knowledge, the analytical method of residues of fluroxypyr-meptyl was not been found in any literature, although numerous of analytical methods for fluroxypyr residues have been published [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the structure of the coating conjugate hapten is routinely used to increase the sensitivity of immunoassays for residue analysis (Harrison et al, 1989;Marco et al, 1995;Schneider and Hammock, 1992;Wie and Hammock, 1984). For example, Johnson and Hall (1996) report an enhancement in sensitivity and reduction in cross-reactivity of a triclopyr ELISA from 5 to 0.1 ng/L by modifying the direct ELISA format from a homologous to a heterologous assay. In cross-reactivity studies, Webb and Hall (2000) also showed that higher concentrations of nonactive cyclohexanediones (IC 50 > 100 µM; Markley et al, 1995; Webb et al, 1997) were required to compete with CCA for antibody binding, as compared with active cyclohexanediones (IC 50 < 100 µM).…”
Section: Rationale For Modification Of Cyclohexadionementioning
confidence: 99%